Founder Mutation in RSPH4A Identified in Patients of Hispanic Descent with Primary Ciliary Dyskinesia - Daniels, M. Leigh Anne; Leigh, Margaret W.; Davis, Stephanie D.; Armstrong, Michael C.; Carson, Johnny L.; Hazucha, Milan; Dell, Sharon D.; Eriksson, Maria; Collins, Francis S.; Knowles, Michael R.; Zariwala, Maimoona A. (Human mutation, 2013)
ABSTRACT Primary ciliary dyskinesia (PCD) is a rare, autosomal recessive, genetically heterogeneous disorder characterized by ciliary dysfunction resulting in chronic oto‐sino‐pulmonary disease, respiratory distress in term neonates, laterality (situs) defects, and bronchiectasis. Diagnosis has traditionally relied on ciliary ultrastructural abnormalities seen by electron microscopy. Mutations in radial spoke head proteins occur in PCD patients with central apparatus defects. Advances in genetic testing have been crucial in addressing the diagnostic challenge. Here, we describe a novel splice‐site mutation (c.921+3_6delAAGT) in RSPH4A, which leads to a premature translation termination signal in nine subjects with PCD (seven families). Loss‐of‐function was confirmed with quantitative ciliary ultrastructural analysis, measurement of ciliary beat frequency and waveform, and transcript analysis. All nine individuals carrying c.921+3_6delAAGT splice‐site mutation in RSPH4A were Hispanic with ancestry tracing to Puerto Rico. This mutation is a founder mutation and a common cause of PCD without situs abnormalities in patients of Puerto Rican descent. Primary ciliary dyskinesia (PCD) is a rare, autosomal recessive, genetically heterogeneous disorder characterized by ciliary dysfunction resulting in chronic otosino‐pulmonary disease, respiratory distress in term neonates, laterality (situs) defects, and bronchiectasis. Here, we describe a novel splice‐site mutation (c.921+3_6delAAGT) in RSPH4A, which leads to a premature translation termination signal in nine Hispanic subjects with Puerto Rican ancestry with PCD. This mutation is a founder mutation and a common cause of PCD without situs abnormalities in patients of Puerto Rican descent.